Progress of integrated traditional Chinese and western medicine nursing in prevention and treatment of infection and infectious diseases (中西医结合护理在传染与感染性疾病防治中的应用进展) - YIN Mengyu (尹梦雨); TIAN Yuan (田媛); LI Mengting (李梦婷); MA Jinghan (马菁浛); TIAN Yiqing (田艺莹); ZHANG Ying (张莹) (中西医结合护理)
The nursing of integrated traditional Chinese and western medicine has played an important role in the prevention and treatment of infection and infectious diseases. This paper reviewed the studies on advantages and implementation of integrated traditional Chinese and western medicine nursing in prevention and treatment of infection and infectious diseases, and provided reference for establishment of integrative nursing plans for infection and infectious diseases. (中西医结合干预在传染与感染性疾病防治中起到了重要的作用。本研究就传染与感染性疾病防治中常见的中西医结合护理方法以及优势进行综述, 旨在为进一步建立和完善传染与感染性疾病的中西医结合护理方案提供参考。)